'At my buried ear': Seamus Heaney's pastoral soundings. Issue 1 (2nd January 2016) - Quément, Fanny
ABSTRACT: This article takes a close look at the sounding process at work in Heaney's pastoral poetry from an eco-critical perspective. Focusing on how Heaney relates to sonic environments in rural places, and on the way he recreates them in poetic language, it shows that Heaney's work calls for an active form of listening. This practice, conscious of the necessity to preserve sound-troves in a way similar to archaeological finds, evolves into a poetic counterintelligence that proves the power of sound. Since Heaney defines sound as an essential element of pastoral poetry, it can be argued that his pastoral poems are sound events in their own right, meant to enter our sonic environment to educate our ears and raise questions of acoustic ecology.